Miocene Planktonic Foraminiferal Biozonation for South Sumatra Basin, Indonesia - Setiadi, Djadjang Jedi; Hendarmawan, .; Sunardi, Edy; Sentani, Eddy Arus; Hutabarat, Johanes (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
Planktonic foraminifera are widely utilized for marine sediments analysis and recent developments in the geochronology of planktonic foraminifera has improved their values as a tool for sedimentary basin analysis. Assessment on the applicability of the “standard” foraminiferal biozonations (e.g., Bolli, 1966; Blow, 1969; and Postuma, 1971) to the biostratigraphy data of the South Sumatra Basin suggests that the standard zones, which are mostly interval-zones defined by first occurrence events, are hardly applicable to the biostratigraphy data derived from the examination of well-cuttings routinely and continuously used in most sedimentary basin studies in Indonesia.The proposed biozonation in this paper were constructed based on two considerations, i.e. information on the biostratigraphy events as indicated in regional- and global-scale biozonation schemes and the occurrence of foraminifera species in the South Sumatra Basin. The correlation between the proposed zonation and that of Blow’s (1969) scheme suggests that the proposed zonation is basically a Blow’s zonation and, accordingly, may be perceived as a modified Blow’s zonation for South Sumatra Basin.